Physiological factors associated with low bone mineral density in female endurance runners. Issue 1 (1st February 2003) - Burrows, M; Nevill, A M; Bird, S; Simpson, D
Abstract : Objective: To explore potential factors that could be associated with low bone mineral density (BMD) in female endurance runners. Methods: Fifty two female endurance runners (1500 m to marathon), aged 18–44 years, took part. Body fat percentage, lumbar spine BMD, and femoral neck BMD were measured using the Hologic QDR 4500w bone densitometer. Data on training, menstrual cycle status, osteoporosis, and health related factors were obtained by questionnaire. Dietary variables were assessed from a prospective seven day dietary record of macronutrients and micronutrients. Results: The mean (SD) lumbar spine and femoral neck BMD were 1.11 (0.11) and 0.89 (0.12) g/cm 2 respectively. A backward elimination regression analysis showed that age, body mass, body fat, distance run, magnesium, and zinc intake were the variables significantly associated with BMD. Lumbar spine BMD (g/cm 2 ) = −1.90 + (0.0486 × age (years)) + (0.342 × log mass (kg)) − (0.000861 × age 2 (years)) − (0.00128 × distance (km/week)), with an R 2 = 30.1% (SEE = 0.089 (95% confidence interval (CI) 0.05 to 0.23); p<0.001). Femoral neck BMD (g/cm 2 ) = −2.51 − (0.00989 × age (years)) + (0.720 × log mass (kg)) + (0.000951 × magnesium (mg/day)) −(0.0289 × zinc (mg/day)) − (0.00821 × body fat (%)) − (0.00226 × distance (km/week)), with an R 2 = 50.2% (SEE = 0.100 (95% CI 0.06 to 0.22); p<0.001). The negative association between skeletal BMD and distance run suggested that participants who ran longer distances had a lower BMD of the lumbar spine and femoral neck. Further, the results indicated a positive association between body mass and BMD, and a negative association between body fat and BMD. Conclusions: The results suggest a negative association between endurance running distance and lumbar spine and femoral neck BMD, with a positive association between body mass and femoral neck and lumbar spine BMD. However, longitudinal studies are required to assess directly the effect of endurance running and body mass on BMD, and to see if the addition of alternative exercise that would increase lean body mass would have a positive effect on BMD and therefore help to prevent osteoporosis.